SARS‐CoV‐2 in animals: susceptibility of animal species, risk for animal and public health, monitoring, prevention and control - EFSA Panel on Animal Health and Welfare (AHAW); Søren Saxmose Nielsen; Julio Alvarez; Dominique Joseph Bicout; Paolo Calistri; Elisabetta Canali; Julian Ashley Drewe; Bruno Garin‐Bastuji; José Luis Gonzales Rojas; Christian Gortázar; Mette Herskin; Virginie Michel; et al. (EFSA Journal, 2023)
Abstract The epidemiological situation of SARS‐CoV‐2 in humans and animals is continually evolving. To date, animal species known to transmit SARS‐CoV‐2 are American mink, raccoon dog, cat, ferret, hamster, house mouse, Egyptian fruit bat, deer mouse and white‐tailed deer. Among farmed animals, American mink have the highest likelihood to become infected from humans or animals and further transmit SARS‐CoV‐2. In the EU, 44 outbreaks were reported in 2021 in mink farms in seven MSs, while only six in 2022 in two MSs, thus representing a decreasing trend. The introduction of SARS‐CoV‐2 into mink farms is usually via infected humans; this can be controlled by systematically testing people entering farms and adequate biosecurity. The current most appropriate monitoring approach for mink is the outbreak confirmation based on suspicion, testing dead or clinically sick animals in case of increased mortality or positive farm personnel and the genomic surveillance of virus variants. The genomic analysis of SARS‐CoV‐2 showed mink‐specific clusters with a potential to spill back into the human population. Among companion animals, cats, ferrets and hamsters are those at highest risk of SARS‐CoV‐2 infection, which most likely originates from an infected human, and which has no or very low impact on virus circulation in the human population. Among wild animals (including zoo animals), mostly carnivores, great apes and white‐tailed deer have been reported to be naturally infected by SARS‐CoV‐2. In the EU, no cases of infected wildlife have been reported so far. Proper disposal of human waste is advised to reduce the risks of spill‐over of SARS‐CoV‐2 to wildlife. Furthermore, contact with wildlife, especially if sick or dead, should be minimised. No specific monitoring for wildlife is recommended apart from testing hunter‐harvested animals with clinical signs or found‐dead. Bats should be monitored as a natural host of many coronaviruses.